Pengembangan Bak Pendaratan Lompat Jauh Dalam Pembelajaran Penjasorkes - Winasis, Probo; Rumini, Rumini (Department of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study is to produce learning tools penjasorkes middle school studentsthrough the development of long jump landing tub. This research is a development. The datacollection was conducted using questionnaires obtained from the evaluation experts and kueionerstudents and use the results of field observations. Technical analysis of the data used isdescriptive percentage. The average yield on the expert validation trials small group obtaineda percentage of 85%, the average yield of the student questionnaire on small group trial wasobtained by 82.37%. Of the average yield of expert validation in a large group trial was obtainedby 94%, while the average yield kueioner students in a large group trial was obtainedby 93.36%. Based on the research results, it can be concluded that the development of thelong jump landing tub is suitable for use in penjasorkes learning for students of SMP N 1Ajibarang.